Rekonstruksi Perlindungan Hukum atas Alat Bukti Hak Ulayat Pasca Berlakunya Peraturan Pemerintah Nomor 18 Tahun 2021 dalam Perspektif Teori Keadilan Prosedural - Safrin Salam; Nuragifah Taheriah; Nurul Miqat; Imron Rizki Azis; A.R. Wirawan (Forschungsforum Law Journal, 2026)
This study examines the reconstruction of legal protection for evidentiary instruments concerning hak ulayat following the enactment of Government Regulation Number 18 of 2021 from the perspective of procedural justice. The primary focus of the study is the delegitimization of customary evidence and the still limited recognition of socio-communal evidence within Indonesia’s land administration system. This research employs a normative legal method using statutory and case approaches. Legal materials are analyzed prescriptively to assess normative consistency, identify regulatory weaknesses, and formulate a fairer model of legal protection for the proof of hak ulayat. The findings show that Government Regulation Number 18 of 2021 has opened a pathway for the formalization of customary land through the schemes of management rights, ministerial determination, registration, and certification. However, this model still places the validity of hak ulayat within a state-centered regime of recognition and has not expressly recognized the history of collective possession, recognition by customary law communities, natural boundaries, and the legitimacy of customary institutions as autonomous components of the national land law system of evidence. From the perspective of procedural law, customary evidence can in fact be associated with documentary evidence, witness testimony, and presumptions. This study concludes that legal certainty over hak ulayat land must be built through a normative reconstruction integrating customary law, land law, and procedural justice so that the protection of the rights of customary law communities becomes more substantive and operational